Usefulness of the NMP22BladderChek Test for Screening and Follow-up of Bladder Cancer - Choi, Hwa Sub (The Korean Urological Association, 2010)
PURPOSE: We evaluated the usefulness of the nuclear matrix protein 22 BladderChek (NMP22BC) test for the screening and follow-up of bladder cancer. MATERIALS AND METHODS: From February 2006 to September 2009, we enrolled 1,070 patients who had hematuria or who were being followed up for bladder cancer. We compared the sensitivity and specificity of the NMP22BC test with those of urine cytology. RESULTS: The sensitivity of the NMP22BC test (77.5%) was significantly higher than that of urine cytology (46.3%). The specificity of the NMP22BC test was 88.8%, compared with 97.9% for urine cytology. The sensitivity of the NMP22BC test (81.8%) in non-muscle-invasive bladder cancer was higher than that of cytology (36.4%). However, the sensitivity of the NMP22BC test and of urine cytology in invasive bladder cancer were 57.1% and 92.9%, respectively. The sensitivity of the NMP22BC test was higher for low-grade bladder cancer (83.9%) than for high-grade (62.5%), and the sensitivity of cytology was higher for high-grade bladder cancer (66.7%) than for low-grade (37.5%). Follow-up bladder cancer was detected in 262 patients. The sensitivity of the NMP22BC test in that group (72.7%) was decreased and the specificity (91.7%) was increased. The sensitivity of cytology (54.5%) in the follow-up group was increased and the specificity (95.6%) was decreased. The presence of pyuria was significantly associated with the lower specificity of the NMP22BC test. CONCLUSIONS: The greater sensitivity of the NMP22BC test may be more useful for the diagnosis of non-muscle-invasive bladder cancer and low-grade bladder cancer than for the diagnosis of invasive or high-grade bladder cancer. If the NMP22BC test is performed in the absence of pyuria, it may play a compensatory role for urine cytology.